Influence of magnetic poles on the properties of field pea (Pisum sativum L.) seed of different ages : Utjecaj magnetnih polova na svojstva sjemena krmnog graška (Pisum sativum L.) različite starosti - Knežević, Dino (Array, 2022)
The study on the influence of magnetic poles on field pea seed of the 'Bera' variety of different ages was carried out under laboratory conditions in a growing chamber. Field pea seed were exposed to a neodymium magnet's positive and negative magnetic poles with a magnetic flux density of 250 mT for 24 hours. Germination of untreated as well as magnetically poled treated seed was carried out according to ISTA rules. Seed characteristics, germination energy, and germination were determined by counting. The root and stem length of the seedlings were measured, and the total length of the field pea seedlings was added up. The total mass of the seedlings was determined by weighing. On average, seed age and magnetic poles significantly (p